Recent topics in nonlinear PDE. II - Masuda, Kyuya; Mimura, Masayasu; ScienceDirect eBooks (Tokyo, Japan : Kinokuniya ; Amsterdam ; New York : North-Holland ; New York, N.Y. : Sole distributor for the U.S.A. and Canada, Elsevier Science Pub. Co., 2005)
This volume is the result of lectures delivered at the second meeting on the subject of nonlinear partial differential equations, held at Tohoku University, 27-29 February 1984. The topics presented at the conference range over various fields of mathematical physics.
Print version record.
Elsevier
Keywords: Differential equations, Partial -- Congresses; Differential equations, Nonlinear -- Congresses; Differential equations, Nonlinear; Differential equations, Partial; Electronic books